Gestión estratégica de recursos humanos, flexibilidad organizativa y encaje estratégico: Implicaciones para la competitividad empresarial (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
Undoubtedly, firms must know how to configure their human resource management systems and practices, with the aim of creating a competitive long-term advantage. To achieve this, they must understand the importance that these human resource management systems and practices achieve two key goals simultaneously: Organisational flexibility and strategic fit. Thus, on the one hand, the strategic human resource management system must allow the adaptation of human resource management practices and proficiency, knowledge and behaviour of the employees, as regards the immediate needs of the firm, which are shown in its organisational strategy. On the other hand, these human resource management systems must favour the development of a dynamic organisational capability, thus generating an ability of response to the needs raised by the actual organisational strategy. To sum up, the strategic human resource management must facilitate strategic flexibility with the aim that the firm reaches a dynamic fit and may answer adequately the requests of the strategy and the environment. The goal of this paper is to analyse how the strategic human resource management can create a sustainable competitive advantage if it includes two essential goals: On the one hand, organisational flexibility, both of resource and coordination, and on the other hand, fit, both external and internal. The achievement of these goals at the same time allows the origination of a dynamic fit, able to create a firm that renews itself, and at the same time, it is given a fast response ability to environmental requests. With the aim of testing these matters, the work is organized in three main sections.
Keywords: Competitiveness; external and internal fit; human capital; human resource management; organisational flexibility and strategy; organisational resources.